Functionally distinct assembly of vascular plants colonizing alpine cushions suggests their vulnerability to climate change - Doležal, Jiří; Dvorsky, Miroslav; Kopecky, Martin; Altman, Jan; Mudrak, Ondrej; Capkova, Katerina; Rehakova, Klara; Macek, Martin; Liancourt, Pierre (Oxford University Press, 2019)
Background and Aims Alpine cushion plants can initially facilitate other species during ecological succession, but later on can be negatively affected by their development, especially when beneficiaries possess traits allowing them to overrun their host. This can be reinforced by accelerated warming favouring competitively strong species over cold-adapted cushion specialists. However, little empirical research has addressed the trait-based mechanisms of these interactions. The ecological strategies of plants colonizing the cushion plant Thylacospermum caespitosum (Caryophyllaceae), a dominant pioneer of subnival zones, were studied in the Western Himalayas. Methods To assess whether the cushion colonizers are phylogenetically and functionally distinct, 1668 vegetation samples were collected, both in open ground outside the cushions and inside their live and dead canopies, in two mountain ranges, Karakoram and Little Tibet. More than 50 plant traits related to growth, biomass allocation and resource acquisition were measured for target species, and the phylogenetic relationships of these species were studied [or determined]. Key Results Species-based trait-environment analysis with phylogenetic correction showed that in both mountain ranges Thylacospermum colonizers are phylogenetically diverse but functionally similar and are functionally different from species preferring bare soil outside cushions. Successful colonizers are fast-growing, clonal graminoids and forbs, penetrating the cushion by rhizomes and stolons. They have higher root-to-shoot ratios, leaf nitrogen and phosphorus concentrations, and soil moisture and nutrient demands, sharing the syndrome of competitive species with broad elevation ranges typical of the late stages of primary succession. In contrast, the species from open ground have traits typical of stress-tolerant specialists from high and dry environments. Conclusion Species colonizing tight cushions of T. caespitosum are competitively strong graminoids and herbaceous perennials from alpine grasslands. Since climate change in the Himalayas favours these species, highly specialized subnival cushion plants may face intense competition and a greater risk of decline in the future.
Keywords: Abiotic stress; alpine; arid; competition; facilitation; global warming; Himalaya; Ladakh; plant-plant interactions; subnival plant communities